WHY WORKPLACE FRIENDSHIPS MATTER: EXAMINING TURNOVER INTENTION AMONG GENERATION Z WORKERS - Angeline, Vania; Zamralita, Zamralita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Workplace friendship, which can be interpreted as an Informal interpersonal relationship built by employees, has various positive impacts and can reduce the intention to leave. Turnover intention describes a person's evaluation of their continued involvement with the company that has not been shown in concrete steps to leave the company. The purpose of this study is to analyze the role of workplace friendship in reducing the turnover rate of generation Z employees. The Workplace friendship variable is measured using the Workplace friendship Scale (WFS) and the turnover Intention variable is measured using the Turnover intention Scale 6 (TIS 6). This study used a non-probability sampling technique, namely convenience sampling. The participants in this study were 210 Generation Z employees with the characteristics of employees who have worked in the age range of 17 - 27 years and have worked at an institution for approximately 1 year. This study uses the JASP 0.19.01 (jeffrey's amazing statistics program) application to process data. The results showed that workplace friendship has a negative relationship with turnover intention with a weak correlation level. ABSTRAKWorkplace friendship yang dapat diartikan sebagai hubungan interpersonal yang bersifat informal dan dibangun oleh karyawan, memiliki berbagai dampak positif dan dapat mengurangi niat untuk keluar. Turnover intention menggambarkan evaluasi seseorang terhadap kelanjutan keterlibatannya dengan perusahaan yang belum ditunjukan ke dalam langkah konkret untuk keluar dari perusahaan. Tujuan dari penelitian ini adalah untuk menganalisis peran workplace friendship dalam mengurangi tingkat turnover terhadap karyawan generasi Z. Variabel Workplace friendship diukur menggunakan Workplace friendship Scale (WFS) dan variabel Intensi Keluar diukur menggunakan Turnover intention Scale 6 (TIS 6). Penelitian ini menggunakan teknik sampling non-probabilitas, yaitu convenience sampling. Peserta dalam penelitian ini adalah 210 karyawan Generasi Z dengan karakteristik karyawan yang sudah bekerja pada rentang usia 17 - 27 tahun dan sudah bekerja siebuah institusi kurang lebih selama 1 tahun. Studi ini menggunakan aplikasi IBM SPSS Statistics versi 25 untuk mengolah data. Hasil penelitian menunjukkan bahwa workplace friendship memiliki hubungan negative dengan turnover intention dengan tingkat korelasi yang lemah.